2021
DOI: 10.1038/s41598-021-95386-9
|View full text |Cite
|
Sign up to set email alerts
|

Steroid, ascorbic acid, and thiamine in adults with sepsis and septic shock: a systematic review and component network meta-analysis

Abstract: To assess the effect from individual component in combinations of steroid, ascorbic acid, and thiamine on outcomes in adults with sepsis and septic shock with component network meta-analysis (NMA). We searched PubMed, EMBASE, and the Cochrane Library Central Register of Controlled Trials from 1980 to March 2021 for randomized controlled trials (RCT) that studied the use of glucocorticoid, fludrocortisone, ascorbic acid, and thiamine in patients with sepsis and septic shock. Citations screening, study selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…These are in line with recent guidelines that advocate for the use of corticosteroids in septic shock [ 31 , 32 ]. However, it may be noted that several meta-analyses showed that vitamin C monotherapy was more beneficial than when administered in combination with corticosteroids [ 13 , 33 ]. Interestingly, the combination of vitamin C and thiamine was associated with a further lower mortality in certain subgroups, while other studies have not shown this finding [ 13 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are in line with recent guidelines that advocate for the use of corticosteroids in septic shock [ 31 , 32 ]. However, it may be noted that several meta-analyses showed that vitamin C monotherapy was more beneficial than when administered in combination with corticosteroids [ 13 , 33 ]. Interestingly, the combination of vitamin C and thiamine was associated with a further lower mortality in certain subgroups, while other studies have not shown this finding [ 13 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be noted that several meta-analyses showed that vitamin C monotherapy was more beneficial than when administered in combination with corticosteroids [ 13 , 33 ]. Interestingly, the combination of vitamin C and thiamine was associated with a further lower mortality in certain subgroups, while other studies have not shown this finding [ 13 , 33 ]. Additional studies are required to determine potential optimized drug combinations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, others have analyzed the role of vitamin C in specific patient populations, such as COVID-19 and respiratory tract infections [ 51 , 52 ]. Several studies have addressed the role of hydrocortisone, ascorbic acid, and thiamine in sepsis [ 53 , 54 , 55 , 56 , 57 ], while others have considered vitamin-C-containing regimens [ 27 , 58 , 59 ]. Some previous studies, which included all regimens containing vitamin C, have indicated a trend toward lower short-term mortality [ 47 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although they increased the incidence of hyperglycemia, GCs reduced the time to shock resolution and the length of mechanical breathing. Although there was no good evidence to support the use of thiamine and ascorbic acid on a regular basis, they were associated with a few side effects [ 18 ].…”
Section: Reviewmentioning
confidence: 99%